2017
DOI: 10.3389/fmicb.2017.02461
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Microbiota of Faba Bean: Functional Characterization of Lactic Acid Bacteria

Abstract: This study investigated the metabolic traits of 27 lactic acid bacteria (LAB) strains belonging to different species, previously isolated from faba bean. The activities assayed, related to technological and nutritional improvement of fermented faba bean, included peptidases, β-glucosidase, phytase, as well as exopolysaccharides synthesis and antimicrobial properties. In addition, the bacteria performance as starter cultures during faba bean fermentation on proteolysis, antioxidant potential, and degradation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 68 publications
1
28
1
Order By: Relevance
“…In a recent work, Verni et al (2017) (Muñoz et al, 2017). None of the strains assayed in the present study showed tannase activity whereas 2 out of 18 strains: Pediococcus pentosaceus CRL2145 and Weissella cibaria CRL2195 showed gallate decarboxylase activity.…”
Section: Proteolytic Activitiescontrasting
confidence: 42%
See 2 more Smart Citations
“…In a recent work, Verni et al (2017) (Muñoz et al, 2017). None of the strains assayed in the present study showed tannase activity whereas 2 out of 18 strains: Pediococcus pentosaceus CRL2145 and Weissella cibaria CRL2195 showed gallate decarboxylase activity.…”
Section: Proteolytic Activitiescontrasting
confidence: 42%
“…(stable LAB consortium and acidification parameters) within 3 to 10 refreshments (Coda et al, 2017;Rizzelo et al, 2014;Vrancken, Rimaux, Weckx, Leroy, & De Vuyst, 2011).…”
Section: Microbiological Ph and Acidity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, vegetables commonly used for pickles contain low protein and high mineral and vitamin contents. As in our study, other studies have assessed the proteolytic activities of vegetable LAB to select starter cultures for legume sourdough ( 21 , 29 ) and pickled vegetables ( 30 ).…”
Section: Resultsmentioning
confidence: 91%
“…This species has not been reported in sourdoughs made with materials other than wheat and rye. For instance, it was not present in sourdoughs made with non‐wheat cereals (Coda, Di Cagno, Gobbetti, & Rizzello, ), including faba‐bean sourdoughs (Verni et al., ) and corn sourdoughs (Wu et al., ). Another reason for it may be the fact that these flours (corn and beans) do not have amylase activity that is important for L. sanfranciscensis to obtain maltose.…”
Section: Prevalence Of L Sanfranciscensis In Sourdoughmentioning
confidence: 99%